Design of a Flow-through Polarographic Sensor Based on Metal Films for Determining N-nitrosodiethanolamine Levels in Rabbit Biological Fluids - Wang, Lai-Hao (Molecular Diversity Preservation International (MDPI), 2006)
The construction and characterization of a flow-through polarographic detector for catalyzing the electroreduction of N-nitrosodiethanolamine (NDELA), is discussed. The flow-through cell is equipped with a gold wire electrode (a thin mercury film deposited on a gold substance). The response is evaluated with respect to substance diameter, length, concentration of modifying film, operating potential, supporting electrolyte and pH, and flow rate in the DC mode. The system allows the determination of N-nitrosodiethanolamine in rabbit biological fluids with relatively inexpensive equipment.